Public participation in development of Kamchanoad’s rice offerings, Naga trees preservation, and Red Lotus Lake popularization - Phukamchanoad, Phusit (Kasetsart Journal of Social Sciences, 2023)
The research aims to explore the preservation approach of “Naga Trees” and the local product development process in order to continue expanding the opportunities in Kamchanoad areas towards public participation. The study also investigates the local folklores which can enhance the charm of the Red Lotus lake and increase its economic value. Questionnaires were distributed and filled out by 400 samples. 27 samples were interviewed, and two focus group discussions were conducted. The findings revealed that the overall level of public participation in Kamchanoad’s local conservation was rated at the highest level, especially in terms of annual village activities such as Grandfather Sri Suttho and Grandmother Sri Pathumma worshipping rituals. The community leaders participated in the Kamchanoad forest preservation at the highest level. The preservation process of Chanoad trees had been prepared for 2 years and 7 months before the cultivation started. The cultivation of Chanoad trees was conducted in the natural setting. Moreover, a local product integrating Kamchanoad folklores or culture was invented. This local product for Grandfather Sri Suttho and Grandmother Sri Pathumma worshipping rituals was the rice offerings (‘Bai Sri’ in Thai) called “Beng Tray of Gifts, Local Rice Offerings”. At the same time, the key charming point of the Red Lotus lake is the beautiful, boundless lotus field. The local people in the Red Lotus Lake’s surrounding areas lived sufficiently in the local way. The local lifestyle was filled with fishing, birdwatching, and living with the priceless natural environment during December-February.